A New Integral Transform With Applications to Fractional Calculus - Chinchole, S. M. (Communications in Mathematics and Applications, 2022)
In this paper, an integral transform with the kernel being the Mittag-Leffler function in two parameters is introduced. Some properties of this integral transform are discussed. Also, its formulae for derivatives of the function are derived. The new integral transform is applied to derive the exact formula for the Laplace transform of fractional derivatives.